The Development Of Animal Monopoly Media On Themes “Objects, Animals And Plants Around Me” In Grade 1 At Mi Al-Ma'arif Sukomulyo - Farah Agista Desydera; Iqnatia Alfiansyah; Nanang Khoirul Umam (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
This development research aims to know the effectiveness of animal monopoly learning media (MONOWAN) theme 7 sub theme 2 about animals around me students in 1st Grade of MI Al-Ma'arif Sukomulyo. The process of developing learning media using a modified and simplified 4-D model is defined, design, develop and without disseminate. The result of the development of learning media in the form of Animal Monopoly. The data source in this development study is class I students MI Al-Ma'arif Sukomulyo who numbered 33 students. Data collection used is validation of learning media validation of learning materials, questionnaire response of students, and test of learning results. With data analysis, the analysis of the validity of learning media, the analysis of the practicality of learning media, and the effectiveness of learning media. Based on the results of descriptive analysis of validation data and trial data obtained that the development of Animal Monopoly learning media for materials on the theme of 7 sub themes 2 learning 1 grade I MI Al-Ma'arif Sukomulyo meets the criteria well, which is as follows : a) The results of validation of learning media performed by validators obtain 81,66% percentage that are categorized in valid and can be used during the learning process , b) Practically categorized from the results of analysis in the practicality of learning media by validators shows that the media can be used with little revision or without revision, c) Categorized effectively from the results of the analysis of learning completeness, the results of the percentage of classical learning completeness of 96,969%, then it can be said that the learning completeness of the learners has been achieved, and the percentage of the results of the student's response to the learning media of Animal Monopoly by 100% can be said to be positive. Keywords: MonopolyAnimals; Learning Media; Second Grade Students; Developing Learning